The Scandal of Continuity in Middle East Anthropology : Form, Duration, Difference - Shryock, Andrew 1963-; Shryock, Andrew 1963-; Scheele, Judith 1978-; Scheele, Judith 1978- (Book collections on Project MUSE., 2019)
Despite a rich history of ethnographic research in Middle Eastern societies, the region is frequently portrayed as marginal to anthropology. The contributors to this volume reject this view and show how the Middle East is in fact vital to the discipline.